45S5-Bioglass®-Based 3D-Scaffolds Seeded with Human Adipose Tissue-Derived Stem Cells Induce In Vivo Vascularization in the CAM Angiogenesis Assay - Handel, Marina; Hammer, Timo R.; Nooeaid, Patcharakamon; Boccaccini, Aldo R.; Höfer, Dirk (Tissue Engineering - Part A, 2013)
Poor vascularization is the key limitation for long-term acceptance of large three-dimensional (3D) tissue engineering constructs in regenerative medicine. 45S5 Bioglass® was investigated given its potential for applications in bone engineering. Since native Bioglass® shows insufficient angiogenic properties, we used a collagen coating, to seed human adipose tissue-derived stem cells (hASC) confluently onto 3D 45S5 Bioglass ®-based scaffolds. To investigate vascularization by semiquantitative analyses, these biofunctionalized scaffolds were then subjected to in vitro human umbilical vein endothelial cells formation assays, and were also investigated in the chorioallantoic membrane (CAM) angiogenesis model, an in vivo angiogenesis assay, which uses the CAM of the hen's egg. In their native, nonbiofunctionalized state, neither Bioglass®-based nor biologically inert fibrous polypropylene control scaffolds showed angiogenic properties. However, significant vascularization was induced by hASC-seeded scaffolds (Bioglass® and polypropylene) in the CAM angiogenesis assay. Biofunctionalized scaffolds also showed enhanced tube lengths, compared to unmodified scaffolds or constructs seeded with fibroblasts. In case of biologically inert hernia meshes, the quantification of vascular endothelial growth factor secretion as the key angiogenic stimulus strongly correlated to the tube lengths and vessel numbers in all models. This correlation proved the CAM angiogenesis assay to be a suitable semiquantitative tool to characterize angiogenic effects of larger 3D implants. In addition, our results suggest that combinations of suitable scaffold materials, such as 45S5 Bioglass ®, with hASC could be a promising approach for future tissue engineering applications. © 2013 Mary Ann Liebert, Inc.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.45s5bi_6